Adsorptive removal of 2,4-dichlorophenoxyacetic acid from aqueous solution using bagasse fly ash as adsorbent in batch and packed-bed techniques - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Clean Technologies and Environmental Policy, 2016)
Among the several synthetic herbicides available currently, 2,4-D is a commonly used herbicide to control broadleaf weeds in agriculture and forestry. However, its increasing use in agricultural and nonagricultural activities has resulted in increasing concentrations of 2,4-D being detected in water bodies. Thus, there is a need to identify methods to remove 2,4-D to protect the environment. Among the various methods used for 2,4-D removal, adsorption is found to be effective, and several adsorbents have been studied to remove 2,4-D from aqueous solutions. In this study, we used bagasse fly ash (BFA), a common industrial waste generated in large amount worldwide, for 2,4-D removal from aqueous solution using batch and continuous packed-bed adsorption. In the batch adsorption process, the effects of initial concentration, contact time, temperature, pH, and particle size of BFA were studied. The packed-bed performance of BFA was investigated by varying the influent concentration (50-150 mg/L), flow rate (1.2-4 mL/min), and bed height (4.5-9 cm). Isotherm and thermodynamic parameters are determined for batch adsorption, whereas the performance of continuous adsorption is evaluated by different packed-bed models. The particle-size effect indicated the higher removal of 2,4-D on the bigger particles of BFA due to greater BET surface area and carbon-to-silica ratio than smaller particles. The maximum percentage removal (37.04) is achieved for an influent concentration of 50 mg/L, flow rate of 1.2 mL/min, and bed height of 6.5 cm. For the first time ever, the deactivation kinetic model was applied for the solid-liquid adsorption system and it showed the best fit among the selected models. The bed capacity (m(2)/g) of BFA is three times greater than synthetic activated carbon for adsorption of 2,4-D. This informs that the BFA can be used as an adsorbent for 2,4-D removal from aqueous solution.